2017
DOI: 10.1039/c7tc02250f
|View full text |Cite
|
Sign up to set email alerts
|

Dual emission and multi-stimuli-response in iridium(iii) complexes with aggregation-induced enhanced emission: applications for quantitative CO2 detection

Abstract: An Ir(iii) complex with AIEE, fluorescence and phosphorescence emission, acid/base sensing in the solid state and quantitative CO2 detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 83 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…Considering these points we examined the applicability of C1 and C3 in CO 2 detection and thoroughly characterized generated CIL by IR and 13 C NMR spectroscopies (Figures S28 and S29). In this direction, solubility of AIE-active luminogens C1 and C3 was scrutinized in various amines like piperidine, pyridine, 1,8-diazabi-cyclo-[5,4,0]-undec-7-ene (DBU), and dimethylamine (DMA). It was observed that these complexes are completely soluble in DMA.…”
Section: Density Function Theory Calculationsmentioning
confidence: 99%
“…Considering these points we examined the applicability of C1 and C3 in CO 2 detection and thoroughly characterized generated CIL by IR and 13 C NMR spectroscopies (Figures S28 and S29). In this direction, solubility of AIE-active luminogens C1 and C3 was scrutinized in various amines like piperidine, pyridine, 1,8-diazabi-cyclo-[5,4,0]-undec-7-ene (DBU), and dimethylamine (DMA). It was observed that these complexes are completely soluble in DMA.…”
Section: Density Function Theory Calculationsmentioning
confidence: 99%
“…[ 75 ] Therefore, a myriad of AIEgens with diverse stimuli‐responsive properties has been developed in recent years, and the resulting materials have shown broad application prospects. [ 76–96 ]…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent d 6 -metal complexes as chemosensors offer certain advantages over many organic probes, including large Stokes shift, long excited–state lifetimes, tunable photo physical/chemical properties, and solubility and stability in aqueous media. Cationic iridium­(III) polypyridine complexes are famed for their excellent tunable photophysical properties. In addition to singlet excited states, due to the involvement of triplet metal-to-ligand charge transfer ( 3 MLCT), triplet ligand-to-ligand charge transfer ( 3 LLCT), and triplet of intraligand state ( 3 IL), they achieved tunable photophysical properties in a predictable way. ,, The alteration of PL band position and intensity due to the specific reactions of analyte with the complex encourage researchers to skillfully design iridium­(III) complex based on analyte approach via the modification in analyte targeting ligand substituents. , …”
Section: Introductionmentioning
confidence: 99%